Study of Legal and Technical Aspect on Sedimentation Management in Indonesia Seas - Muhammad Ilman Hadiid; Andi Febrianto; Eko Prasetiyo; Ayi Tarya; Eka Djunarsjah (International Journal Labs, 2026)
Dredging and marine sand export activities in Indonesia have raised concerns about their impacts on marine environmental quality and regulatory certainty in sedimentation management. This study examines the legal and technical aspects of marine sedimentation management policies, focusing on the implementation of Government Regulation No. 26 of 2023 on Marine Sedimentation Management and Government Regulation No. 31 of 2021 on Shipping. The legal review evaluates the coherence of these regulations with higher legal frameworks, including Law No. 32 of 2014 on Marine Affairs, the Job Creation Law, the United Nations Convention on the Law of the Sea (UNCLOS 1982), and international standards from the Oslo-Paris (OSPAR) Convention. The analysis reveals that PP 26/2023 and PP 31/2021 still exhibit vertical inconsistencies, overlapping institutional mandates, and limited alignment with international marine governance principles. Technically, this study analyzes changes in water turbidity using Sentinel-2 satellite imagery and the Normalized Difference Turbidity Index (NDTI) across four priority areas: Pulau Karimun Besar, Demak Regency, Kutai Kartanegara Regency, and Surabaya City. The findings indicate a strong, statistically significant correlation between NDTI values and marine sand export volume in Pulau Karimun Besar (r = 0.99; p = 0.0005), while other locations show weaker, non-significant correlations. These results highlight the need to integrate legal reform with spatially informed technical monitoring to enhance sustainable sedimentation management in Indonesia’s coastal waters.